Modeling the impact of logistic performance, economic features, and demographic factors of countries on the seaborne trade - Alireza Mahpour; Iman Farzin; Amirhossein Baghestani; Sina Ashouri; Zahra Javadi; Latifeh Asgari (Asian Journal of Shipping and Logistics (AJSL), 2023)
The shipping industry continues to have strong growth prospects due to increased efficiency and economic liberalization. Through seaborne trade, port infrastructure and logistics impact economic growth in developing countries. This makes studying the factors affecting seaborne trade for such countries particularly important. The current paper aims at analyzing the impact of logistics, economic, and demographic variables on seaborne commodity trade between Qatar, Oman, Turkey, Pakistan, and Iran. Employing a gravity model, results show that a 1% improvement in Logistics Performance Index (LPI) consignments in the importing country can result in a 0.8% increase in total trade flows. Based on results, a 1% increase in the tariff rate reduces the value of trade by 0.4%. Furthermore, a 0.5% increase in trade is caused by the increase in population of the destination country. A sensitivity analysis also shows that logistics variables are more significant than economic and demographic variables. It can be concluded that trade policymakers in developing countries can get better results by improving logistics performance and investing on logistics infrastructure leads to more trade.
Keywords: 650; Developing countries; Gravity model; LPI; Middle-east; Seaborne trade; Tariff